Double-masked trial of topical acyclovir and steroids in the treatment of herpes zoster ocular inflammation. Issue 9 (September 1991) - Marsh, R J; Cooper, M
Abstract : Ninety seven new patients with ophthalmic zoster were randomly allocated to three topical treatment groups: acyclovir (ACV) ointment and placebo drops (AP), placebo ointment with steroid drops (PS), and acyclovir ointment with steroid drops (AS). The dosage administered was determined by the score of the ocular inflammation. Follow-up was for at least one year. The results showed that topical ACV alone is insufficient for severe ocular inflammation but is not inclined to lead to recurrences in milder cases. Topical steroid alone is effective but tends to necessitate prolonged treatment. Combined steroid and ACV is questionably better than steroid alone and causes marginally fewer rebound inflammations.